Analysis of Student Critical Thinking Skills Improvement Profile through SETS Based Physics E-Book Intervention Integrated with Local Wisdom - Irawan, Nisya Indriyanti; Pujianto, Pujianto (Universitas Lambung Mangkurat, 2026)
The integration of the SETS (Science, Environment, Technology, and Society) approach within a Physics E-book based on 'Nenggala' local wisdom enables students to bridge scientific concepts with cultural reality, fostering contextual understanding, while the SETS model provides structured stages of investigation that stimulate critical inquiry. The development of this integrated E-book serves as the primary contribution of this research, addressing the significant gap in students' critical thinking skills, particularly in analysis, inference, and evaluation. Employing a Research and Development (R&D) method with the ADDIE model, this study evaluated the media’s effectiveness through a Non-Equivalent Pretest-Posttest Group Design involving 108 grade XI students. The results demonstrate that the E-book is highly feasible and significantly effective; the experimental group utilizing the SETS model achieved the most substantial improvement with an N-gain of 70.9 (high category), markedly outperforming the control group. These findings indicate that SETS-based E-books integrated with local wisdom provide an innovative reference for educators to strengthen the Merdeka Curriculum while fostering meaningful physics learning and higher-order thinking skills.